YOUTH AGAINST RELIGIOUS RADICALISM: AN INTRARELIGIOUS APPROACH IN KOMUNITAS SANTRI BATANG IN KABUPATEN BATANG, JAWA TENGAH - Faqih, Ahmad; Umar, Achmad Jauhari (IAIN Palangka Raya, 2022)
Youth is a part of the structure of society that is vulnerable to being exposed to radicalism. According to a report from the Setara Institute 2011-2012, cases of intolerance that occur in Indonesia are often committed by youth, especially high school age teenagers. In 2017, there has been a spread of religious radicalism doctrine in Batang carried out by several religious leaders towards high school youth age. In response to that, a group of youths in Batang formed a youth community aimed to counteract the spread of radicalism in Batang, Komunitas Santri Batang (KSB). This study wants to see the extent to which the role of youth represented by the KSB against religious radicalism by campaigning for the idea of 'religious moderation'. This study formulates two problems related to the role of youth in campaigning for religious moderation, (1) What is the strategy of the KSB in promoting religious moderation idea? (2) how effective are the programs organized by the KSB related to the prevention of radicalism among youth groups? To answer these questions, the researcher will interview several members of the KSB and participants of the KSB programs. The results of this study indicate that there is synergy between the KSB youth and several agencies in cultivating moderation and diversity dialogue among the community. This can be seen through the KSB community strategy in countering religious radicalism using an inclusive approach and social engagement dialogue. Also, KSB pays attention to strengthening intra-religious relations by involving various youths from different religious mass organization backgrounds in several activities. This strategy is considered effective to counter religious radicalism which often attacks young people.